Who are the people? Refugees and access to Danish citizenship - Bech, Emily Cochran; Jensen, Kristian Kriegbaum; Mouritsen, Per; Olsen, Tore Vincents (Politica, 2017)
Denmark has some of the most restrictive citizenship rules in Europe, with requirements for long residence, language, knowledge, self-support and crime. Citizenship implies voting rights and the right to stand for election in national elections. As such it determines full democratic inclusion. Today, approximately 376,000 adult residents lack Danish citizenship. Using public registry data we investigate whether refugees who arrived as adults in 2001-09 have been able to fulfil the language, self-support and criminal record requirements. We investigate which requirements are most exclusionary, and what difference it makes if they were made less demanding. We further examine how many residents with Danish citizenship are able to meet these requirements. On this basis, we discuss their implications for Danish democracy, and whether they are consistent with normative conceptions of fairness.